D-amphetamine and antipsychotic drug effects on latent inhibition in mice lacking dopamine D2 receptors - Bay-Richter, C.; O'Callaghan, M.J.; Mathur, N.; O'Tuathaigh, C.M.P.; Heery, D.M.; Fone, Kevin C.F.; Waddington, J.L.; Moran, P.M. (Nature Publishing Group, 2013)
Drugs that induce psychosis, such as D-amphetamine (AMP), and those that alleviate it, such as antipsychotics, are suggested to exert behavioral effects via dopamine receptor D2 (D2). All antipsychotic drugs are D2 antagonists, but D2 antagonism underlies the severe and debilitating side effects of these drugs; it is therefore important to know whether D2 is necessary for their behavioral effects. Using D2-null mice (Drd2/), we first investigated whether D2 is required for AMP disruption of latent inhibition (LI). LI is a process of learning to ignore irrelevant stimuli. Disruption of LI by AMP models impaired attention and abnormal salience allocation consequent to dysregulated dopamine relevant to schizophrenia. AMP disruption of LI was seen in both wild-type (WT) and Drd2/. This was in contrast to AMP-induced locomotor hyperactivity, which was reduced in Drd2/. AMP disruption of LI was attenuated in mice lacking dopamine receptor D1 (Drd1/), suggesting that D1 may play a role in AMP disruption of LI. Further supporting this possibility, we found that D1 antagonist SKF83566 attenuated AMP disruption of LI in WT. Remarkably, both haloperidol and clozapine attenuated AMP disruption of LI in Drd2/. This demonstrates that antipsychotic drugs can attenuate AMP disruption of learning to ignore irrelevant stimuli in the absence of D2 receptors. Data suggest that D2 is not essential either for AMP to disrupt or for antipsychotic drugs to reverse AMP disruption of learning to ignore irrelevant stimuli and further that D1 merits investigation in the mediation of AMP disruption of these processes.